A randomized, open‐label, multicentre, phase 2/3 study to evaluate the safety and efficacy of lumiliximab in combination with fludarabine, cyclophosphamide and rituximab versus fludarabine, cyclophosphamide and rituximab alone in subjects with relapsed chronic lymphocytic leukaemia. (8th August 2014) - Awan, Farrukh T.; Hillmen, Peter; Hellmann, Andrzej; Robak, Tadeusz; Hughes, Steven G.; Trone, Denise; Shannon, Megan; Flinn, Ian W.; Byrd, John C.; the LUCID trial investigators
Summary Lumiliximab is a chimeric monoclonal antibody that targets CD23 on the surface of chronic lymphocytic leukaemia (CLL) B‐cells. Early phase clinical studies with lumiliximab alone and in combination with fludarabine, cyclophosphamide and rituximab (FCR) established its potential efficacy and tolerability. The 152CL201 trial [Lumiliximab with fludarabine, cyclophosphamide and rituximab (FCR) versus FCR alone in subjects with relapsed CLL; LUCID] was a phase 2/3, randomized (1:1), open‐label, multicentre study of lumiliximab in combination with FCR versus FCR alone in patients with relapsed CLL. Six hundred and twenty‐seven patients were randomized to either arm. Overall the combination of lumiliximab with FCR was not significantly better than FCR alone (overall response rate 71% vs. 72%, complete response rate 16% vs. 15%, median progression‐free survival 24.6 vs. 23.9 months respectively, for FCR with and without lumiliximab). There was a slightly increased incidence of adverse events with lumiliximab but these increases did not appear to lead to differences in eventual outcomes. An interim analysis failed to show sufficient efficacy of the combination of lumiliximab with FCR. The study was therefore stopped early for lack of efficacy. Despite the eventual outcome, the LUCID trial is one of the largest studies that provides valuable insight into the efficacy and tolerability of FCR as a therapeutic option for patients with relapsed CLL.